Laparoscopic versus open appendicectomy for complicated appendicitis: A prospective study - Padankatti L; Pramod R; Gupta A; Ramachandran P (Wolters Kluwer Medknow Publications, 2008)
Aims: The purpose of this study was to compare open versus laparoscopic appendicectomy (LA) in complicated appendicitis. Materials and Methods: We prospectively analyzed all children over a 2-year period who underwent appendicectomy in a single institution and found 30 cases of complicated appendicitis diagnosed on the table and confirmed by histopathology. These children were allocated randomly into Group 1 if they had LA and Group 2 if they had open appendicectomy (OA), solely based on surgeon assessment. The parameters assessed were duration of symptoms before surgery, use of postoperative parenteral analgesia, timing of initiation of feeds after surgery, postoperative complications and duration of postoperative stay. Results: Of the 30 patients with complicated appendicitis, 12 patients in Group 1 underwent LA and 18 patients in Group 2 underwent OA. The two groups were comparable for age and sex. Children in Group 1 were found to need less parenteral analgesia (two out of 12 versus six out of 18). Postoperatively, feeds were started earlier in Group 1 than in Group 2 (2.5 days versus 3.7 days). The average postoperative hospital stay was 5 days in Group 1 and 7.5 days in Group 2. There were only minor wound infections in Group1 as against two major complications in Group 2. There was no mortality in either group. Conclusions: In complicated appendicitis, laparoscopic approach carries definite advantages with less postoperative morbidity and hospital stay. It is a feasible and better alternative than the open approach in complicated appendicitis.